IIn Silico Testing On The Activity Of Flavonol In Sterculia foetida Leaf As Natural Anti Hyperlipidemia Compounds - Nindrahayu Syam; Andi Ariyandy; Ika Yustisia; Sulfahri; Yusfina (Hasanuddin University, 2022)
This study aims to measure the biological activity of flavonols in the leaves of Sterculia foetida as an antihyperlipidemic drug. The chemical structure of flavonols contained in the leaves of Sterculia foetida was taken from the literature. The target protein used was 3-hydroxy 3-methylglutaryl coenzyme A reductase and the control was simvastatin. Water molecules have been removed with PyMol v2.5.2 Software. Docking between the target protein and flavonols was performed using PyRx-Python Prescription 0.8 Software. The results showed that flavonol compounds have greater potential for antihyperlipidemia compared to control compounds. The equivalent affinity of 3-hydroxy 3-methylglutaryl coenzyme A reductase for flavonols is -8.3, and the affinity of 3-hydroxy-3-methylglutaryl coenzyme A reductase for simvastatin is -7.9. Flavonol toxicity studies have shown that flavonols are not potentially carcinogenic and did not cause mutations. The absorption of flavonols in water was higher than that of the control compound.